Global research trends on the links between gut microbiota and radiotherapy: a bibliometric analysis (2004-2023) - Wang, Shuyuan; Yuan, Zhen; Gao, Xiaohui; Wu, Jiaxing; Ren, Yifan; Yu, Xiufeng; Li, Jianxiong; Wei, Wei (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundThere is a crosstalk between gut microbiota and radiotherapy. The aim of this study is to use bibliometric analysis to explore the research status and development trends of research on gut microbiota and radiotherapy.MethodsA literature search regarding publications on gut microbiota and radiotherapy from 2004 to 2023 was retrieved. CiteSpace and VOSviewer were used to conduct the bibliometric analysis. The growth rate of publications, leading countries and institutions, preferred journals, top authors and co-cited authors, top co-cited references, keywords and citation were analyzed in this study.ResultsA total of 2821 papers were extracted. The number of papers has increased rapidly over the past decade, especially after 2017. The USA and China had the most publications and made great contributions to this field. The Chinese Academy of Sciences stood out as the institution with the highest number of publications, followed by the Chinese Academy of Medical Sciences & Peking Union Medical College. The most influential authors were Fan Saijun and Li Yuan. PLoS One had the most publications and the most total citations. Highly cited papers and high-frequency keywords illustrated the current status and trends. Furthermore, analysis of keyword with burst revealed that immunotherapy, acid, intestinal barrier, therapy, immunotherapy, fecal microbiota transplantation, etc, are at the forefront of research in this area.ConclusionThis study provides an overview of research on gut microbiota and radiotherapy, highlighting influential contributors, impactful publications, and emerging trends. Our finding suggests avenues for further exploration to improve clinical outcomes.